Dynamics of ethnic relations in Malaysia - Jawan, Jayum; Boyman, Siti Noranizahhafizah; Kadam Kiai, Stanley Bye (UPM Press, 2020)
This research sought to understand and affirm key factors that helped shape ethnic relations in a multi-cultural, ethnic and religious Malaysia. Samples were drawn from three public institutions of higher learning, namely Universiti Putra Malaysia (UPM), Universiti Malaysia Sarawak (UNIMAS) and Universiti Pendidikan Sultan Idris (UPSI) and compared to see whether different settings had significant influence on how samples responded to ethnic relations-related constructs. Findings indicated that (1) some societal structures needed to be transformed further to provide opportunities for various ethnic interaction; (2) in many instances, student samples’ preferences were ethnically influenced; (3) nature of the environment that the student samples were in could Influence their preferences. Therefore, policymakers need to be aware of these societal impediments and the dire need to introduce a relevant policy to address these shortcomings. Public policies for inter-ethnic relations must be formulated based on the bottom-up input, i.e. listening to people on the ground, for the former to be effective in nation-making.